Information Assurance in the Era of Mobility: Challenges and Solutions - Amin, Mohammad Hasan; Neoaz, Nahid (BULLET : Jurnal Multidisiplin Ilmu, 2024)
With more family and organizational members using mobile devices within homes and workplaces, mobile device security particularly in regard to information security is an important question. The information assurance principles, secure mobile technologies, trends, threats, policies and compliance in mobile systems are presented in this article. These basic features including cryptos, MFA, MDM, and SC are part of the mobile security technologies explained in the paper. It also looks into how these latest trends, for instance 5G networks, IoT, mobile payment and AI app impact and offer opportunities as well as risks. Therefore, the article discusses policy regimes and compliance and the emergence of threats such as mobile malware, phishing, and ransom ware. However, it also proscribes comprehension of future opportunities and further evolutions in the sphere of mobile information assurance including the creation of Artificial Intelligence, quantum-safe encryption, and the international cooperation in order to overcome the new threats on the horizon. The mobile systems adopted by different systems and software may prone to several hacking attacks, although, through proper policies’ integration and up-to-date technologies, mobile systems security is feasible than in the advancing technology world.